2020
DOI: 10.1016/j.heliyon.2020.e04623
|View full text |Cite
|
Sign up to set email alerts
|

An overview on human serum lectins

Abstract: An extensive literature survey done on the various naturally occurring lectins in human serum upon its salient features such as methods of detection, level and sites of synthesis, binding specificity, cation dependency, modes of isolation, molecular and functional characterization way back from 1930s to till date was presented in a tabulated section. In addition, the generation of lectin and other immune molecules in vertebrates upon treatment with exogenous elicitors has also been framed in a tabular form. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 207 publications
0
7
0
Order By: Relevance
“…We found that chitosan‐ and scUCF‐isolated material contains little, if any, signal for these high‐abundance plasma proteins (Figure 4b). Next, we performed Western blot analyses to detect human lectins that are present in plasma at high abundance (Beulaja Manikandan et al., 2020) and may co‐isolate in EV preparations, including H‐Ficolin (FCN3), tetranectin (TETN), and serum amyloid A (SAA (Supplemental Figure S3). Protein lysates from plasma collected pre‐ and post‐chitosan incubation were included as controls.…”
Section: Resultsmentioning
confidence: 99%
“…We found that chitosan‐ and scUCF‐isolated material contains little, if any, signal for these high‐abundance plasma proteins (Figure 4b). Next, we performed Western blot analyses to detect human lectins that are present in plasma at high abundance (Beulaja Manikandan et al., 2020) and may co‐isolate in EV preparations, including H‐Ficolin (FCN3), tetranectin (TETN), and serum amyloid A (SAA (Supplemental Figure S3). Protein lysates from plasma collected pre‐ and post‐chitosan incubation were included as controls.…”
Section: Resultsmentioning
confidence: 99%
“…These may interact with the glycans of the IL‐6 glycoforms temporarily and thus delay binding to the IL‐6R during the liver passages. Besides a soluble IL‐6 receptor [27] (affecting all IL‐6 variants equally) blood serum of mammals also contains soluble versions of the ASGPR, [28] MR, [29] the group of lectins of the lectin pathway of complement activation [30] and various additional soluble lectins [31] . These mostly multivalent lectins should preferentially interact with IL‐6 glycoforms bearing larger multibranched glycans and might cause a delayed targeting of lectin‐associated IL‐6 glycoforms to the liver.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the rapid clearance of IL-6 from blood (t 1/2 % 3min) ag lycosidase-based degradation of the N-glycans (observed after % 24 h) [26] is unlikely to occur during the plasma lifetime of the different IL-6 glycoforms.T hus,b oth the faster and the slower plasma clearance of the IL-6 glycoforms relative to reference IL-6 E.coli can only be ac onsequence of the different carbohydrate chains.W e assume the following scenario:S ince reference IL-6 E.coli is rapidly targeted to the liver the delayed clearance of most IL-6 glycoforms should be caused by lectins in the plasma, on blood cells or blood vessels.T hese may interact with the glycans of the IL-6 glycoforms temporarily and thus delay binding to the IL-6R during the liver passages.B esides asoluble IL-6 receptor [27] (affecting all IL-6 variants equally) blood serum of mammals also contains soluble versions of the ASGPR, [28] MR, [29] the group of lectins of the lectin pathway of complement activation [30] and various additional soluble lectins. [31] These mostly multivalent lectins should preferentially interact with IL-6 glycoforms bearing larger multibranched glycans and might cause ad elayed targeting of lectin-associated IL-6 glycoforms to the liver. Thel ess branched smaller glycans are presumably not well bound by the serum lectins but may still be recognized by lectins in the liver leading to an accelerated overall clearance of these glycoforms.T he serum concentration of the human lectins of the lectin pathway of complement activation was found to be in the range of 1-20 mgmL À1 .…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Due to the rapid clearance of IL-6 from blood (t 1/2 % 3min) ag lycosidase-based degradation of the N-glycans (observed after % 24 h) [26] is unlikely to occur during the plasma lifetime of the different IL-6 glycoforms.T hus,b oth the faster and the slower plasma clearance of the IL-6 glycoforms relative to reference IL-6 E.coli can only be ac onsequence of the different carbohydrate chains.W e assume the following scenario:S ince reference IL-6 E.coli is rapidly targeted to the liver the delayed clearance of most IL-6 glycoforms should be caused by lectins in the plasma, on blood cells or blood vessels.T hese may interact with the glycans of the IL-6 glycoforms temporarily and thus delay binding to the IL-6R during the liver passages.B esides asoluble IL-6 receptor [27] (affecting all IL-6 variants equally) blood serum of mammals also contains soluble versions of the ASGPR, [28] MR, [29] the group of lectins of the lectin pathway of complement activation [30] and various additional soluble lectins. [31] These mostly multivalent lectins should preferentially interact with IL-6 glycoforms bearing larger multibranched glycans and might cause ad elayed targeting of lectin-associated IL-6 glycoforms to the liver. Thel ess branched smaller glycans are presumably not well bound by the serum lectins but may still be recognized by lectins in the liver leading to an accelerated overall clearance of these glycoforms.T he serum concentration of the human lectins of the lectin pathway of complement activation was found to be in the range of 1-20 mgmL À1 .…”
Section: Methodsmentioning
confidence: 99%